Impact Of Physical Activity On Metabolic Dysfunction Associated Steatohepatitis Patients: A Scoping Review - G, Ramya; Yogeshwari, R.; Sridevi, S.; Kumar, T. Senthil; Venkatesh, N. (Journal of Neonatal Surgery, 2025)
Background: Metabolic Dysfunction Associated Steatohepatitis is a progressive liver condition characterized by excessive liver fat, inflammation, and fibrosis, which can lead to cirrhosis, liver failure, and liver cancer. Methods: A Systematic search was conducted in PubMed, Scopus, GoogleScholar, and PeDro by using Boolean search with keywords. Studies from 1972 to 2025 were included. Selection criteria required studies to be peer-reviewed and focus on exercise interventions in MASH patients. Exclusion criteria included studies involving animals, non-interventional research, non-English publications, and conference abstracts. The PRISMA approach guided the selection process, and data were analyzed based on exercise type, duration, intensity, and effects on liver function and metabolic markers. Results: Ten studies were included, in which aerobic and resistance exercise that reduces liver fat, improves insulin sensitivity, and decrease systemic inflammation. Moderate-to-vigorous intensity exercise for at least 150 minutes per week was associated with liver health improvements, even without weight loss. However, inconsistencies in study methodologies and participant characteristics led to mixed findings. Conclusion: Physical activity plays an important role in managing MASH, offering benefits for liver function and metabolic health. The lack of standardized exercise protocols underscores the need for further research. Future studies should focus on long-term randomized controlled trials to refine exercise recommendations and assess their impact on disease progression.